Arthroscopic Coracoclavicular Ligament Reconstruction Using Graft Augmentation and Titanium Implants - Juha O. Ranne; Terho U. Kainonen; Jussi A. Kosola; Lasse L. Lempainen; Kari J. Kanto; Janne T. Lehtinen (Elsevier B.V., 2022)
Several techniques have been introduced to treat acromioclavicular separation with coracoclavicular ligament reconstruction using graft augmentation. A modified arthroscopic technique for coracoclavicular ligament reconstruction was used based on a previous technique where the supportive device and tendon graft share the clavicular and coracoid drill holes. A notable problem with the previous technique was large protruding suture knots on the washer and clavicle, which could predispose to wound infection. In this modified technique, titanium implants were introduced. The implants hid the suture knot on the clavicle, and less foreign material was needed between the clavicular and coracoid implants.